2023
DOI: 10.1021/acsomega.3c05445
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Gradient in Polymer Coating by Reactive Layer-by-Layer Assembly on Solid Substrate

Sezer Özenler,
Ali Ata Alkan,
Ufuk Saim Gunay
et al.

Abstract: The study describes a simple yet robust methodology for forming gradients in polymer coatings with nanometer-thickness precision. The thickness gradients of 0–20 nm in the coating are obtained by a reactive layer-by-layer assembly of polyester and polyethylenimine on gold substrates. Three parameters are important in forming thickness gradients: (i) the incubation time, (ii) the incubation concentration of the polymer solutions, and (iii) the tilt angle of the gold substrate during the dipping process. After e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…More specifically, the gradient structure of an organic electrically conductive material, poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), was developed in application areas such as wearable smart electronics and optoelectronics . Further, polyethylenimine (PEI) is a synthetic cationic material, and the gradient structure has been used in many applications such as nanofiltration membranes and cell adhesion . However, the gradient structures in these applications mostly exist through the thickness and/or use lab-scale methods that are not scalable and inefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the gradient structure of an organic electrically conductive material, poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), was developed in application areas such as wearable smart electronics and optoelectronics . Further, polyethylenimine (PEI) is a synthetic cationic material, and the gradient structure has been used in many applications such as nanofiltration membranes and cell adhesion . However, the gradient structures in these applications mostly exist through the thickness and/or use lab-scale methods that are not scalable and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Further, polyethylenimine (PEI) is a synthetic cationic material, and the gradient structure has been used in many applications such as nanofiltration membranes 22 and cell adhesion. 23 However, the gradient structures in these applications mostly exist through the thickness and/or use lab-scale methods that are not scalable and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we make use of PEL thickness asymmetry, which is different from PEL charge asymmetry used in bipolar channels; 64 in fact, our method is based on a new grafting technique developed recently for a layer-by-layer PEL coating that allows for a thickness gradient. 65 The efficacy of the proposed design is compared with PEL-covered conical nanochannels by numerically solving the governing equations including the Poisson, Nernst–Planck, and Stokes–Brinkman equations. It is shown that the proposed design can provide a higher degree of ICR than conical nanochannels over a wide range of ion concentrations, and its efficiency is more pronounced for higher values of the PEL-fixed charge concentration.…”
Section: Introductionmentioning
confidence: 99%
“…While the findings reported herein appear to be somewhat conceptual, recent advancements in surface engineering, fabrication, and functionalization in general indeed evidence their practicality. Specifically, the development of a simple yet robust methodology of forming gradients in polymer coatings with nanometer thickness precision by a reactive layer-by-layer assembly via modulating the incubation time, the incubation concentration of the polymer solutions, and the tilt angle of the substrate during the dipping process is a promising point in this respect. Our proposed method shares some features with previous research works exploiting geometrical asymmetry, with ,, or without PEL coating, to enhance RED power generation.…”
Section: Introductionmentioning
confidence: 99%